Improving institutional childbirth services in rural Southern Tanzania: a qualitative study of healthcare workers' perspective. Issue 9 (22nd September 2016) - Jaribu, Jennie; Penfold, Suzanne; Manzi, Fatuma; Schellenberg, Joanna; Pfeiffer, Constanze
Abstract : Objective: To describe health workers' perceptions of a quality improvement (QI) intervention that focused on improving institutional childbirth services in primary health facilities in Southern Tanzania. Design: A qualitative design was applied using in-depth interviews with health workers. Setting: This study involved the Ruangwa District Reproductive and Child Health Department, 11 dispensaries and 2 health centres in rural Southern Tanzania. Participants: 4 clinical officers, 5 nurses and 6 medical attendants from different health facilities were interviewed. Results: The healthcare providers reported that the QI intervention improved their skills, capacity and confidence in providing counselling and use of a partograph during labour. The face-to-face QI workshops, used as a platform to refresh their knowledge on maternal and newborn health and QI methods, facilitated peer learning, networking and standardisation of care provision. The onsite follow-up visits were favoured by healthcare providers because they gave the opportunity to get immediate help, learn how to perform tasks in practice and be reminded of what they had learnt. Implementation of parallel interventions focusing on similar indicators was mentioned as a challenge that led to duplication of work in terms of data collection and reporting. District supervisors involved in the intervention showed interest in taking over the implementation; however, funding remained a major obstacle. Conclusions: Healthcare workers highlighted the usefulness of applying a QI approach to improve maternal and newborn health in rural settings. QI programmes need careful coordination at district level in order to reduce duplication of work.